The Effect of Racial Socialization on Urban African American Use of Child Mental Health Services - Bannon, William M. (2008)
OBJECTIVE: To examine how parental endorsement of racial socialization parenting practices relates to child mental health service use among an urban sample of African American families. METHODS: A cross-sectional sample of urban African American parents (n = 96) provided ratings of their beliefs concerning various dimensions of racial socialization constructs, i.e., spiritual or religious coping (SRC), extended family caring (EFC), cultural pride reinforcement (CPR), and assessed regarding their use of child mental health services. RESULTS: At the multivariate level, the use of child mental health services was significantly positively associated with moderate levels of endorsement of SRC and EFC. Inversely, scores in the moderate range of CPR were associated with a reduced likelihood of child mental health service use. CONCLUSION: Parental endorsement of racial socialization parenting practices appear to play a salient role in child mental health service use among an urban African American families. Further research with larger and more representative samples should be pursued.